Impact of a pyridazine derivative on tripartite synapse ultrastructure in hippocampus: a three-dimensional analysis - Xu, Zan; Foster, Joshua B.; Lashley, Rashelle; Wang, Xueqin; Benson, Emily; Kidd, Grahame; Lin, Chien-liang Glenn (Frontiers in Cellular Neuroscience, 2023)
We previously discovered a pyridazine derivative compound series that can improve cognitive functions in mouse models of Alzheimer's disease. One of the advanced compounds from this series, LDN/OSU-0215111-M3, was selected as the preclinical development candidate. This compound activates local protein translation at the perisynaptic astrocytic process (PAP) and enhances synaptic plasticity sequentially. While biochemical evidence supports the hypothesis that the compound enhances the structural plasticity of the tripartite synapse, its direct structural impact has not been investigated. To address this gap, we used volume electron microscopy to study the hippocampal tripartite synapse three-dimensional structure in mice after LDN/OSU-0215111-M3 compound treatment. We found that the compound increased the size of tertiary apical dendrites, the volume of mushroom spines, the proportion of mushroom spines containing spine apparatus, and alterations in the spine distribution across the surface area of tertiary dendrites. This compoundLDN/OSU-0215111-M3 also increased the number of the PAP interacting with the mushroom spines as well as the size of the PAP in contact with the spines. Furthermore, proteomic analysis of the isolated synaptic terminals indicated an increase in dendritic and synaptic proteins as well as suggested a possible involvement of the phospholipase D signaling pathway. To further validate that the LDN/OSU-0215111-M3 compound altered synaptic function, electrophysiological studies showed increased long-term potentiation following compound treatment. In summary, this study provides direct evidence that pyridazine derivatives enhance the structural and functional plasticity of the tripartite synapse.